Identification and Phylogenetic Analysis of Blue Swimming Crab (Portunus sp.) in The Northern Waters of Jepara Used DNA Barcoding - Lazuardhi, Risqi; Sabdaningsih, Aninditia; Ayuningrum, Diah; Saputra, Suradi Wijaya; Hartoko, Agus; Haeruddin, Haeruddin (Al-Kauniyah: Jurnal Biologi, 2025)
The Awur Bay and Kartini Beach in Jepara, Central Java, are fishing areas with blue swimming crab as a main catch. This study aims to examine the species of blue swimming crabs captured in the Northern Waters of Jepara from different locations, analyze the molecular characteristics based on gender differences, obtain GenBank accession numbers as genetic conservation, and construct their phylogenetic tree. The research used a quantitative descriptive method. Samples were collected using purposive sampling from fishermen's catches and selected based on the difference in crab claws and carapace color, with a total of 4 samples. The samples were extracted using a DNA extraction kit and tested using Polymerase Chain Reaction (PCR) to visualize mitochondrial DNA (COI gene) and processed using MEGA 11. BLAST results showed that the similarity of the samples to Portunus pelagicus ranged from 97.02% to 99.42%. The different colors of claws and carapace did not affect the DNA sequence composition, hence indicating sexual dimorphisms. The DNA sequences from this study were deposited to GenBank with accession number LC836055.1-LC836058.1. Based on the phylogenetic tree construction, the clade of all samples shows a close relationship with the species Portunus pelagicus.